Ações educativas de enfermeiras em estratégias de saúde da família - Donaduzzi, Joanita Cechin (2009)
Health education is a process that aimed to contribute to formation and development of the people s critical conscious. It is in order to search solutions and organization of the collective action and the change of the reality. In this way, the practice of health education needs to be intrinsic in the nurse s assistance daily in the Family Health Strategy (FHS). He/she needs to prior actions of health promotion in a practice that gathered the popular and scientific knowledge. This study aimed to characterize the education actions developed by these nurses and to discuss the theoretical conceptions that lead these practice. It is a qualitative study with an ethnographic approach developed in 2 units of FHS in southern Brazil. The data were produced through triangulation, using three techniques: participant observation, ethnographic interview and documental analysis. The data was analyzed using the French stream of discourse analysis. The analytical tools used were: metaphor, polissemy and paraphrase. The interviews analysis linked with the field diary notes and the documental analysis to drive the characterization of education actions of the nurses of FHS. After that 2 categories emerged: the health education in the FHS nurses work daily and educative practice developed of nurses in the FSH and the autonomy of the users. The results pointed out that education actions developed by nurses ranging, mainly, between a hygienist and technician practice centered in the traditional pedagogical trend. In the other hand, they have discursive marks near to critical pedagogy referential. We perceived an ideological conflict and an ethical dilemma between the discourse (theory) and the practice of these nurses. We recommend the necessity of an educational practice in health more effectiveness that could involve the community through a participative process. The educational practice could permit to them a critical reflection about the reality and about the factors determinants to live healthier